Nonlinear optimal control for a business cycles macroeconomic model of linked economies. Issue 2 (3rd April 2018) - Rigatos, G.; Siano, P.; Loia, V.; Ghosh, T.; Krawiec, A.
ABSTRACT: The article proposes nonlinear optimal control for a multi-agent Kaldor-Kalecki macroeconomic model of linked economies. The Kaldor-Kalecki model has been analysed mostly by considering closed economies in which interactions with other economies or financial institutions are overlooked. In the present article, a system of linked economies is considered in which the Kaldor-Kalecki model of each individual economy is retrofitted with a fraction of the GDP produced by the other economies. In this context a nonlinear optimal control scheme is developed for the entire financial system consisting of the interacting economies. The global stability properties of the control method are proven through Lyapunov analysis.